The Exploring the Use of Phoenix Wright: Ace Attorney Trilogy as a Visual Novel Game to Enhance EFL Learners’ Vocabulary and Motivation - Fikra Nur Firman; Lidiyatul Izzah (MEDIA DIDAKTIKA, 2025)
This study explores the integration of Phoenix Wright: Ace Attorney Trilogy, a visual novel game, into English as a Foreign Language (EFL) learning to enhance students’ vocabulary acquisition and motivation. Conducted with 39 ninth-grade students at SMPN 19 South Tangerang, this research employed an explanatory sequential mixed-methods design. Quantitative data were collected through pre-test and post-test vocabulary assessments and analyzed using the Wilcoxon Signed Ranks Test. Qualitative data were obtained through questionnaires and semi-structured interviews to investigate learners’ perceptions and experiences. The findings revealed a statistically significant improvement in vocabulary mastery after the intervention, with mean scores increasing from 43.97 to 86.44 (p < 0.05). Qualitative results supported this improvement, indicating that students found vocabulary learning through the game enjoyable, contextual, and memorable. They also expressed higher motivation, self-confidence, and positive attitudes toward learning English. These findings align with Krashen’s Input Hypothesis, Constructivist Learning Theory, and Gardner’s Instrumental Motivation Theory, suggesting that narrative-driven digital games can effectively enhance both vocabulary acquisition and learner motivation. The study concludes that visual novel games, when integrated purposefully into classroom practice, provide a meaningful and engaging alternative to traditional vocabulary instruction.